A comparison of a traditional endotracheal tube versus ETView SL in endotracheal intubation during different emergency conditions: A randomized, crossover cadaver trial. Issue 44 (November 2016) - Truszewski, Zenon; Krajewski, Paweł; Fudalej, Marcin; Smereka, Jacek; Frass, Michael; Robak, Oliver; Nguyen, Bianka; Ruetzler, Kurt; Szarpak, Lukasz
Abstract: Background: Airway management is a crucial skill essential to paramedics and personnel working in Emergency Medical Services and Emergency Departments: Lack of practice, a difficult airway, or a trauma situation may limit the ability of paramedics to perform direct laryngoscopy during cardiopulmonary resuscitation. Videoscope devices are alternatives for airway management in these situations. The ETView VivaSight SL (ETView; ETView Ltd., Misgav, Israel) is a new, single-lumen airway tube with an integrated high-resolution imaging camera. To assess if the ETView VivaSight SL can be a superior alternative to a standard endotracheal tube for intubation in an adult cadaver model, both during and without simulated CPR. Methods: ETView VivaSight SL tube was investigated via an interventional, randomized, crossover, cadaver study. A total of 52 paramedics participated in the intubation of human cadavers in three different scenarios: a normal airway at rest without concomitant chest compression (CC) (scenario A), a normal airway with uninterrupted CC (scenario B) and manual in-line stabilization (scenario C). Time and rate of success for intubation, the glottic view scale, and ease-of-use of ETView vs. sETT intubation were assessed for each emergency scenario. Results: The median time to intubation using ETView vs. sETT was compared for each of the aforementioned scenarios. For scenario A, time to first ventilation was achieved fastest for ETView, 19.5 [IQR, 16.5–22] sec, when compared to that of sETT at 21.5 [IQR, 20–25] sec (p = .013). In scenario B, the time for intubation using ETView was 21 [IQR, 18.5–24.5] sec (p < .001) and sETT was 27 [IQR, 24.5–31.5] sec. Time to first ventilation for scenario C was 23.5 [IQR, 19–25.5] sec for the ETView and 42.5 [IQR, 35–49.5] sec for sETT. Conclusions: In normal airways and situations with continuous chest compressions, the success rate for intubation of cadavers and the time to ventilation were improved with the ETView. The time to glottis view, tube insertion, and cuff block were all found to be shorter with the ETView. Trial Registration: clinicaltrials.gov Identifier: NCT02733536.